2023
DOI: 10.1073/pnas.2216975120
|View full text |Cite
|
Sign up to set email alerts
|

Collective magnetotaxis of microbial holobionts is optimized by the three-dimensional organization and magnetic properties of ectosymbionts

Abstract: Over the last few decades, symbiosis and the concept of holobiont—a host entity with a population of symbionts—have gained a central role in our understanding of life functioning and diversification. Regardless of the type of partner interactions, understanding how the biophysical properties of each individual symbiont and their assembly may generate collective behaviors at the holobiont scale remains a fundamental challenge. This is particularly intriguing in the case of the newly discovered magnetotactic hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…For a given population of cells forming an organism, the average alignment , where θ is the angle between the field direction and the magnetization of the organism) is a function dependent on the strength of the magnetic torque produced by the chain and the thermal energy of the fluid’s Brownian motion. Some authors ( 36 ) consider that to offer any biological advantage to a magnetotactic organism, . Even in a basic model containing only three particles under a weak magnetic field of 6 μT, the alignment condition is fulfilled in all of our simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a given population of cells forming an organism, the average alignment , where θ is the angle between the field direction and the magnetization of the organism) is a function dependent on the strength of the magnetic torque produced by the chain and the thermal energy of the fluid’s Brownian motion. Some authors ( 36 ) consider that to offer any biological advantage to a magnetotactic organism, . Even in a basic model containing only three particles under a weak magnetic field of 6 μT, the alignment condition is fulfilled in all of our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…However, they also showed that alignment in sediment pores is much less efficient compared to MT performing magnetotaxis in the water column. As we cannot determine the living environment, we can simply compare the Brownian alignment in a low magnetic field (as stated above) to be as efficient as that of modern MT (e.g., Magnetobacterium bavaricum ) ( 6 ) and magnetotactic holobionts ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the idea that symbiotic magnetic sensing as a collaboration between MTB and host adaptations has gained increasing support [105]. In fact, magnetoreceptive bacteria have been found to be capable of transferring their capacities by producing a collective magnetic fieldassisted motility guided by a chemoaerotaxis system in the holobiont [106].…”
Section: Microbes and Various Types Of Magnetic Fieldsmentioning
confidence: 99%